(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2018)
A special mammography homemade ionization chamber was developed to be applied for mammography energy range dosimetry. This chamber has a total sensitive volume of 6 cm³ and is made of a PMMA body and graphite coated collecting electrode. Performance tests as saturation, ion collection efficiency, linearity of chamber response versus air kerma rate and energy dependence were determined. The results obtained with this special homemade ionization chamber are within the limits stated in international recommendations. This chamber can be used in quality control programs of mammography energy range. All measurements were carried out at the Calibration Laboratory of IPEN.